The Influence of Motherhood Guidance on The Personality of Islamic Teenagers in Sidodadi Village, Sekampung District, East Lampung Regency - Muhyidin Thohir (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
Housewives have a very important role and responsibility, especially in nurturing and guiding their children to become a high-quality generation with good Muslim personalities. Whether this role is performed well or not has a significant impact on the growth and development of Muslim teenagers' personalities. Therefore, mothers must be more active in guiding their children in accordance with Islamic teachings. The research question in this study is “Does the guidance of housewives have an influence on the personalities of Muslim adolescents in Sidodadi Village, Sekampung District, East Lampung Regency?” The purpose of this study is to determine whether the guidance of housewives has an influence on the personalities of Muslim adolescents in Sidodadi Village, Sekampung District, East Lampung Regency. The methods used are the questionnaire method as the primary method, and observation, interviews, and documentation as supporting methods. The population in this study consists of all Muslim adolescents, totaling 470 children. Since the number exceeds 100, the researcher used random sampling, selecting a representative sample of 47 children. To analyze the data, the author used the Chi-Square formula (X). The calculated Chi-Square (X) was found to be greater than the Chi-Square (X) table value at both the 1% significance level and the 5% significance level, or 9.48813.227. This proves that there is an influence, indicating a strong correlation between the guidance of housewives and the personality of Islamic adolescents.